Pituitary Adenylate Cyclase Activating Polypeptide Has Inhibitory Effects on Melanoma Cell Proliferation and Migration In Vitro - Hajdú, Tibor; Kovács, Patrik; Zsigrai, Emese; Takács, Roland; Vágó, Judit; Cho, Sinyoung; Sasi-Szabó, László; Becsky, Dániel; Keller-Pinter, Aniko; Emri, Gabriella; Rácz, Kálmán; Reglodi, Dora; et al. (Frontiers in Oncology, 2021)
Pituitary adenylate cyclase activating polypeptide (PACAP) is an endogenous neuropeptide which is distributed throughout the body. PACAP influences development of various tissues and exerts protective function during cellular stress and in some tumour formation. No evidence is available on its role in neural crest derived melanocytes and its malignant transformation into melanoma. Expression of PACAP receptors was examined in human skin samples, melanoma lesions and in a primary melanocyte cell culture. A2058 and WM35 melanoma cell lines, representing two different stages of melanoma progression, were used to investigate the effects of PACAP. PAC1 receptor was identified in melanocytes in vivo and in vitro and in melanoma cell lines as well as in melanoma lesions. PACAP administration did not alter viability but decreased proliferation of melanoma cells. With live imaging random motility, average speed, vectorial distance and maximum distance of migration of cells were reduced upon PACAP treatment. PACAP administration did not alter viability but decreased proliferation capacity of melanoma cells. On the other hand, PACAP administration decreased the migration of melanoma cell lines towards fibronectin chemoattractant in the Boyden chamber. Furthermore, the presence of the neuropeptide inhibited the invasion capability of melanoma cell lines in Matrigel chambers. In summary, we provide evidence that PACAP receptors are expressed in melanocytes and in melanoma cells. Our results also prove that various aspects of the cellular motility were inhibited by this neuropeptide. On the basis of these results, we propose PACAP signalling as a possible target in melanoma progression.